Analyzing frequency and spectrum of chlorophyll mutation induced through Gamma ray and Combination treatment (Gamma + EMS) on genetic paradigm of Artemisia annua L. - RAJANI SINGH; Girjesh Kumar (Caryologia, 2022)
For the development of genetic programs with novel characteristics induced mutagenesis has been used extensively. Chlorophyll mutations are considered as the most dependable indices for assessing the efficiency of different mutagens in inducing the genetic variability in crop plants and are also used as genetic markers in basic and applied research. In the present scenario of high health susceptibility, the global demand for natural medicine derived from plant species has   increased enormously. Sweet wormwood (Artemisia annuaL.) – an important medicinal plant species with immense remedial values, was selected for the present study and exposed to gamma rays  at 100 Gy, 200 Gy, 300 Gy and combination treatments with 100 Gy + 0.1%EMS, 200 Gy + 0.1% EMS, 300 Gy + 0.1%EMS. Meiotic study was also done and various cytological aberrations were observed in M2 generation  like stickiness, precocious, scattering, laggard and bridge etc. The frequency of induced chl mutation varied in different mutagen treatments. Eight different types of chl mutants namely albina, chlorina, xantha, aurea, viridis, yellow viridis and tigrina etc. were recorded in M2 generation on plant population basis. The frequency of xantha mutants was quite high in both the treatments but in gamma exposed set it was followed by albina whereas in combination treatments viridis was second highest mutant. In different mutants quantitative analysis of chl pigments was also done and content was highest in viridis i.e. 3.86µg/ml FW and lowest in albina i.e. 0 µg/ml FW . Although chl mutations thought to be lethal in nature, but present study has proven to be a milestone in identifying the threshold dose of a mutagen that would increase the genetic variability and induces new trait.